Si/Ti2O3/Reduced Graphene Oxide Nanocomposite Anodes for Lithium-Ion Batteries with Highly Enhanced Cyclic Stability - Park, A. Reum; Son, Dae-Yong; Kim, Jung Sub; Lee, Jun Young; Park, Nam-Gyu; Park, Juhyun; Lee, Joong Kee; Yoo, Pil J. (American Chemical Society, 2015)
Silicon (Si) has attracted tremendous attention as a high-capacity anode material for next generation Li-ion batteries (LIBs); unfortunately, it suffers from poor cyclic stability due to excessive volume expansion and reduced electrical conductivity after repeated cycles. To circumvent these issues, we propose that Si can be complexed with electrically conductive Ti2O3 to significantly enhance the reversible capacity and cyclic stability of Si-based anodes. We prepared a ternary nanocomposite of Si/Ti2O3/reduced graphene oxide (rGO) using mechanical blending and subsequent thermal reduction of the Si, TiO2 nanoparticles, and rGO nanosheets. As a result, the obtained ternary nanocomposite exhibited a specific capacity of 985 mAh/g and a Coulombic efficiency of 98.4% after 100 cycles at a current density of 100 mA/g. Furthermore, these ternary nanocomposite anodes exhibited outstanding rate capability characteristics, even with an increased current density of 10 A/g. This excellent electrochemical performance can be ascribed to the improved electron and ion transport provided by the Ti2O3 phase within the Si domains and the structurally reinforced conductive framework comprised of the rGO nanosheets. Therefore, it is expected that our approach can also be applied to other anode materials to enable large reversible capacity, excellent cyclic stability, and good rate capability for high-performance LIBs.